Efektivitas Model Lesson Study dalam Penerapan Pembelajaran Konstruktivisme pada SMA/MA Di Kabupaten Kutai Barat Provinsi Kalimantan Timur Tahun 2012 - Zeni Haryanto (Universitas Pendidikan Ganesha, 2013)
Based on the mapping of the standard competence/basic competence of students in each subject is mainly targeted at schools in West Kutai regency into the sample obtained by the fact that over 50% of the standard of competence in each subject cannot be reach by the UN students. It is necessary for improvement in the standard of the learning process to conduct training on constructivist learning for teachers of each subject and implemented through the lesson study model. The model consists of lesson study phase of Plan, Do and See. The results of the learning observations is then discussed in the reflection on the stage See to know what needs to be improved in the teaching and learning activities of students at the time. Based on the analysis of the instrument can be concluded that a guide of the lesson study model is produced that can be applied to implement school-based lesson study in West Kutai District with the effectiveness of the implementation by 91%, or can be said to be very effective. Keywords: Effectiveness, Lesson Study Model, Learning, Constructivism